2020
DOI: 10.1002/art.41489
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Severe Fatigue Following Nuclease Therapy in Patients With Primary Sjögren’s Syndrome: A Randomized Clinical Trial

Abstract: Objective. To assess the safety and efficacy of RSLV-132, an RNase Fc fusion protein, in a phase II randomized, double-blind, placebo-controlled clinical trial in patients with primary Sjögren's syndrome (SS). Methods. Thirty patients with primary SS were randomized to receive treatment with RSLV-132 or placebo intravenously once per week for 2 weeks, and then every 2 weeks for 12 weeks. Eight patients received placebo and 20 patients received RSLV-132 at a dose of 10 mg/kg. Clinical efficacy measures included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 27 publications
1
27
0
3
Order By: Relevance
“…Our data is consistent with the recent reports that increased fatigue scores are associated with lower serum levels of proinflammatory cytokines [ 7 , 12 , 13 ], and that improvement in fatigue in response to a nuclease therapy was associated with an increase in IFN modular activity in pSS patients [ 14 ]. Taken together, our findings challenge the presumed mechanisms of action of HCQ [ 15 ] and prompt further investigations into the role of IFN activity in pSS pathobiology.…”
Section: Discussionsupporting
confidence: 93%
“…Our data is consistent with the recent reports that increased fatigue scores are associated with lower serum levels of proinflammatory cytokines [ 7 , 12 , 13 ], and that improvement in fatigue in response to a nuclease therapy was associated with an increase in IFN modular activity in pSS patients [ 14 ]. Taken together, our findings challenge the presumed mechanisms of action of HCQ [ 15 ] and prompt further investigations into the role of IFN activity in pSS pathobiology.…”
Section: Discussionsupporting
confidence: 93%
“…Hydroxychloroquine, DHEA, and rituximab failed to improve fatigue in controlled studies (35,37,38). The RSLV-132, an RNase Fc fusion protein, in a phase II study showed improvement of severe fatigue as determined by four independent patient-reported measures of fatigue (33). Ongoing clinical trials are testing new targets on fatigue in pSS, such as, Lanraplenib (GS-9876), Filgotinib (GS-6034), Tirabrutinib (GS-4059), CDZ173, and VIB4920 (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…There are many noncoding RNAs in human circulation that have inflammatory gene regulatory functions. It was hypothesized that a reduction of these circulating RNAs in patients with pSS might have a positive effect on symptoms such as fatigue and indeed, the study showed improvement of severe fatigue by four independent patientreported measures (33).…”
Section: Treatment Of Fatigue Pharmacological Treatmentmentioning
confidence: 90%
See 1 more Smart Citation
“…A total of 12 articles (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) published between 2014 and 2020 that met the inclusion criteria were included in the analysis, containing a total of 450 subjects from 13 trials. The detailed literature screening process is shown in Figure 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%